2019
DOI: 10.1007/jhep06(2019)008
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric superfluids

Abstract: We present a complete classification of symmetric superfluids, namely shift-symmetric and Poincaré invariant scalar field theories that have an enlarged set of classically conserved currents at leading order in derivatives. These theories arise in the decoupling limit of the effective field theory of shift-symmetric, single-clock cosmologies and our results pick out all models with couplings fixed by additional symmetry. Remarkably, in D ≥ 2 spacetime dimensions there are only two possibilities: the Dirac-Born… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 71 publications
(126 reference statements)
1
62
0
Order By: Relevance
“…It isn't obvious whether one can construct an 'improved' traceless stress tensor [24][25][26][27][28], but it seems highly unlikely in the full nonlinear theory 2 . See [24,29] for discussions on this point in similar theories. Therefore these cases are scale but not conformal invariant (i.e.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It isn't obvious whether one can construct an 'improved' traceless stress tensor [24][25][26][27][28], but it seems highly unlikely in the full nonlinear theory 2 . See [24,29] for discussions on this point in similar theories. Therefore these cases are scale but not conformal invariant (i.e.…”
Section: )mentioning
confidence: 99%
“…It is easy to extend the the above analysis of solids that realize SI to a simpler case, namely a SI relativistic superfluid, which consists in a single scalar field that has a temporal vev for the gradient, Ψ = t + ψ. This case has also been studied in [29]. The most general action at leading order in derivatives is S = d d xP (X (Ψ) ) where X (Ψ) ≡ ∂ µ Ψg µν ∂ ν Ψ.…”
Section: Scale Invariant Superfluidsmentioning
confidence: 99%
“…It belongs to a subclass of scalar-tensor theories where the Lorentz invariance is broken [18][19][20][21] and can be extended into more general class [22]. Aspects of symmetry in cuscuton gravity is studied in [23]. In particular, it has been shown that cuscuton gravity is useful in cosmology [24,25], for instance, a healthy bouncing solution without instabilities were realized [26].…”
mentioning
confidence: 99%
“…Consider the action S[φ] with a variational global symmetry group G and a vacuum solution φ 0 (x). In the active form, the symmetry group G acts on the fields φ(x) as 82) while the coordinates do not transform. A symmetry transformation for which g • φ 0 (x) = φ 0 (x) is broken by the vacuum field configuration.…”
Section: Spontaneous Symmetry Breaking and Nonlinear Realizationsmentioning
confidence: 99%
“…Jacobi identities ensure that the algebra up to first-order is that of the four-dimensional conformal algebra. It is not possible to extend the conformal algebra with the addition of G 2 apart from in two space-time dimensions (see for [82] more details.). Due to the lack of shift symmetry and Adler's zero for the scalar, there is no sense in which the resulting EFT of the dilaton has an enhanced soft limit.…”
Section: Single Scalar Goldstone Modesmentioning
confidence: 99%